Impact of Manager Roles in Achieving Organizational Excellence - العبادي هاشم فوزي; حمدالله اسامة علاء (Journal of Economics and Administrative Sciences, 2018)
The current research problem is focused on the level of human resource managers’ performance of their contemporary roles and the impact of this on achieving organizational excellence. The research aims at diagnosing and interpreting the nature of the relationship between the roles of human resource manager and organizational excellence. ), And oil companies located in Baghdad governorate. The research included (boards of directors), and collected data from (83) respondents representing the research community exclusively and comprehensively represented in the positions of function (Directors-General, Associate Directors-General, heads of departments, divisions and divisions). (49) questions, as well as the method of personal interview to support the results of the questionnaire and achieve the greatest realism in the collection of information, and sought to test a number of the main hypotheses derived from sub-hypotheses to see the relationship of correlation and influence between the variables of research, The research reached a number of conclusions, the most important of which was the existence of a significant correlation between HR roles and organizational excellence, as well as a significant relationship of influence to the role of human resource manager in organizational excellence. To discuss the results of the development of a set of recommendations, the most important of which is the need for companies to provide support and support to human resources managers in the implementation of their roles more effectively and efficiently, and the possibility of increasing opportunities to achieve organizational excellence, and the need to benefit from the company’s attention to all standards of organizational excellence, To develop future plans and mechanisms to achieve more attention to these standards.